BESARNYA RISIKO KEGEMUKAN TERHADAP TEKANAN DARAH - Sihadi -; Sri Poedji Hastoety Djaiman (Persagi, 2006)
Backgrounds: Consuming an excessive amount of energy from carbohydrate, fat and protein can lead to obesity. There are relations between overweight and hypertension, therefore the analyses that determine the risk of overweight to the blood pressure level is conducted. Objectives: To determine the relationship between the level of overweight and blood pressure level. Methods: The data used is secondary data from Health Household Survey (SUSENAS) 2004. All samples have been analyzed are male and female with age between 25 - 65 years. Results: After controlled with several variables in the model, the result of the analysis shows that people with Overweight and obesity have the risk of 1. 79 and 2 .38 times compared to nonnal people to get borderline blood pressure respectively. Beside that, Overweight and obesity have the risk of 2.51 and 5.19 times compared to normal people to get high blood pressure respectively. Another variable female have the risk of 1.45 times compared to males to get high blood pressure. The person with age 36-45 years and 46-65 years have the risk of 1.33 and 1.68 times compared to the person aged 25-35 to get borderline blood pressure respectively. In addition, the person with age 36-45 years and 46-65 years have the risk of 1.84 and 3.64 times compared to the person age 25-35 to get high blood pressure respectively. Conclusions: Overweight persons have the risk of both having high blood pressure ( 160/100 mmHg) and borderline blood pressure level (130-159/85-99 mmHg). Female have higher risk of high blood pressure than males. Age above 36 years have higher risk of high blood pressure than 25-35 years old. Recommendations: Programme in controlling blood pressure should be targeted to community especially those who are overweight, female and older than 36 years. (Pen el Gizi Makan 2006, 29(2): 78-84]